2021
DOI: 10.1002/nop2.1111
|View full text |Cite
|
Sign up to set email alerts
|

Pain management and coping strategies for primary dysmenorrhea: A qualitative study among female nursing students

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Deduplication and title and abstract screening were performed using Covidence (2022) software. The eligibility of the remaining articles was determined through full-text screening.…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Deduplication and title and abstract screening were performed using Covidence (2022) software. The eligibility of the remaining articles was determined through full-text screening.…”
Section: Search Strategymentioning
confidence: 99%
“…However, 15%–40% of NSAIDs users experienced adverse effects (e.g., nausea, abdominal pain), leading to 10% of medicine modification or withdrawal (Guimarães & Póvoa, 2020; Vonkeman & van de Laar, 2010). Other concerns regarding pharmaceutical use are medication tolerance and reliance (Fernández‐Martínez et al, 2022). Additionally, 20%–25% of women are nonresponsive to NSAIDs (Wang et al, 2013), whereas others may have contraindications against NSAIDs (e.g., gastrointestinal problems; Ferries‐Rowe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nursing Students in Southern Spain by Abreu-Sánchez et al [15] revealed that the prevalence of dysmenorrhea was 73.8% (of which 63.3% had primary dysmenorrhea and 10.5% had secondary dysmenorrhea), and that it was more common in women with longer menstrual cycles, heavier bleeding, and those who did not use oral hormonal contraception (OCP). In their qualitative study of female nursing students, Fernández-Martneze et al [16] (2022) found four pain management and coping techniques for primary dysmenorrhea: pain management strategies; utilising painkillers; selecting the best treatment; and non-pharmacological therapies. They came to the conclusion that nursing students had trouble treating primary dysmenorrhea, self-medicated, were reluctant to consult a doctor, tried non-pharmacological methods, and sought counsel from other women in their family or social group.…”
Section: Menstrual Characteristics and Symptoms Inmentioning
confidence: 99%
“…With regard to the use of distractions, such as watching television or listening to music becomes habitual in self-care for dysmenorrhea. Other strategies have been shown to be effective in reducing menstrual pain such as hot compresses, regulating diet and acupressure (Fernández-Martínez et al, 2021). The mechanism of acupuncture can be an alternative in women who are not interested in pharmacological treatment, involving the stimulation of nerve fibers and receptors in complex interactions with endorphins and serotonin (Guimarães & Póvoa, 2020).…”
Section: Non-pharmacologicalmentioning
confidence: 99%